2011
DOI: 10.1038/nsmb.2191
|View full text |Cite
|
Sign up to set email alerts
|

The extracellular chaperone clusterin sequesters oligomeric forms of the amyloid-β1−40 peptide

Abstract: In recent genome-wide association studies, the extracellular chaperone protein, clusterin, has been identified as a novel risk factor in Alzheimer's disease (AD). We have examined the interactions between clusterin and the AD-associated amyloid-β 1-40 peptide (Aβ 1-40 ) which is prone to aggregate into an ensemble of oligomeric intermediates implicated in both the proliferation of amyloid fibrils and in neuronal toxicity. Using highly sensitive single molecule fluorescence methods, we have found that Aβ 1-40 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
311
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(335 citation statements)
references
References 45 publications
21
311
2
1
Order By: Relevance
“…CD2AP is an adaptor molecule involved in dynamic actin remodeling and membrane trafficking, and CLU encodes clusterin, which is a molecular chaperone,39 is present in senile plaques, and has been shown to modulate Aβ oligomer assembly 40. We previously reported rare SNPs and small structural variants within the CLU gene that were associated with LOAD 41…”
Section: Discussionmentioning
confidence: 99%
“…CD2AP is an adaptor molecule involved in dynamic actin remodeling and membrane trafficking, and CLU encodes clusterin, which is a molecular chaperone,39 is present in senile plaques, and has been shown to modulate Aβ oligomer assembly 40. We previously reported rare SNPs and small structural variants within the CLU gene that were associated with LOAD 41…”
Section: Discussionmentioning
confidence: 99%
“…Because oligomeric species formed under such conditions consist predominantly of non-β-structures, it is interesting to speculate that nature might have evolved a portfolio of chaperones to target specifically both the non-β-as well as the conventional β-aggregated forms to curtail pathological aggregation. Recent evidence suggests that such a situation might, indeed, occur for extracellular chaperones (70,71). Although these simulations focused on the Aβ1-42 peptide, we expect aspects of the mechanism proposed here to be applicable to other amyloid proteins, such as the prion protein or α-synuclein.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the concomitant inhibition of oligomer toxicity and increased oligomer size induced by chaperones, via recruitment of more misfolded protein oligomers into the aggregates, has been interpreted to mean that chaperoneinduced clustering of oligomers is a strategy used by chaperones to inhibit oligomer toxicity (Ojha et al, 2011;Mannini et al, 2012, Binger et al, 2013Cascella et al, 2013a). By contrast, using single-molecule fluorescence techniques, it has been shown that clusterin and Bc are able to bind preformed oligomers of A and sequester them from dissociation or further growth into fibrils, revealing another possible mechanism of action of molecular chaperones which is binding in the absence of aggregate clustering (Narayan et al, 2011;Narayan et al, 2012). In the case of Clu, the formation of complexes with misfolded proteins is thought to be relevant in the in vivo clearance of these aberrant species via membrane-associated receptors, such as the LRP-2 receptor (Hammand et al, 1997;Cole and Ard, 2000;Bartl et al, 2001).…”
Section: Discussionmentioning
confidence: 99%